Anger and disgust shape judgments of social sanctions across cultures, especially in high individual autonomy societies - Andersson, P. A.; Vartanova, I.; Västfjäll, D.; Tinghög, G.; Strimling, P.; Wu, J.; Hazin, I.; Akotia, C. S.; Aldashev, A.; Andrighetto, G.; Anum, A.; Arikan, G.; et al. (Scientific Reports, 2024)
When someone violates a social norm, others may think that some sanction would be appropriate. We examine how the experience of emotions like anger and disgust relate to the judged appropriateness of sanctions, in a pre-registered analysis of data from a large-scale study in 56 societies. Across the world, we find that individuals who experience anger and disgust over a norm violation are more likely to endorse confrontation, ostracism and, to a smaller extent, gossip. Moreover, we find that the experience of anger is consistently the strongest predictor of judgments of confrontation, compared to other emotions. Although the link between state-based emotions and judgments may seem universal, its strength varies across countries. Aligned with theoretical predictions, this link is stronger in societies, and among individuals, that place higher value on individual autonomy. Thus, autonomy values may increase the role that emotions play in guiding judgments of social sanctions.